Lecturer Strategic Planning in the Development of Innovative E-Learning Platforms at Widya Gama Mahakam University in Samarinda City - Hanim, Zaenab; Bali Geroda, Godefridus; Marhani, Marhani; Ruslan, Ruslan (Educationist: Journal of Educational and Cultural Studies, 2023)
Strategic Planning in education, especially in higher education, is a critical component in maintaining the quality and relevance of education. FKIP Lecturer (Faculty of Teaching and Education) of Widya Gama Mahakam Samarinda University has an essential role in planning Strategic platform development and innovation. This article aims to discuss planning strategies that can be carried out by FKIP UWGM lecturers in developing platform-learning innovation at the University. Strategic planning and innovation approaches are used to understand the steps that FKIP lecturers can take to achieve these goals. This research uses a qualitative approach with a descriptive approach. The results of this study indicate that FKIP lecturers need strategic planning in developing an e-learning platform, including needs analysis, instructional design, technology used, and learning evaluation. Strategic planning by FKIP lecturers in developing innovative e-learning platforms is essential to improve the quality of learning. Through proper planning, lecturers can provide learning experiences that meet student needs, integrate appropriate technology, and conduct effective evaluations.